Geomythology, caves, and tourism: history and future perspectives. (12th May 2023) - Antić, Aleksandar; Mayor, Adrienne
The main goal of this study is to explore the current understanding of geomythology and its potential interactions and future perspectives in cave tourism destinations. The study includes a theoretical overview of geomythology, ancient stories and myths about the origin and events in caves around the world, the concept of tourist caves (show caves), and the use of geomythology for cave tourism storytelling. Considering the diversity of geomythology and ancient cave myths, it is evident that future cave tourism interpretation should be directed toward searching out mytho-historical narratives that captivate visitors. The analysis showed that geomythology can provide a unique and powerful way to promote and modernise the presentation of special caves for exciting and ethical tourism development.